DAMPAK REVITALISASI RPTRA DAN PENATAAN PKL TERHADAP TINGKAT KEBAHAGIAAN WARGA KOTA PEMATANGSIANTAR - Bahrudi Efendi Damanik (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
The purpose of this study was to determine the impact of RPTRA Revitalization on the happiness level of city residents, to know the impact of street vendor arrangement on the happiness level of the city and to determine the impact of RPTRA Revitalization and PKL Structuring on the happiness level of city residents. This research can be classified as an associative type of research, the sample in this study was 272 people for an error level of 10%, the sampling technique used was incidental sampling. The results of this study are RPTRA revitalization partially has a positive and significant effect on the level of happiness of city residents, t-count> t-table (5.046> 1.969), partially PKL structuring has a positive and significant effect on the level of happiness of city residents, t-count> t-table (8,452> 1,969), there is a positive and significant influence between the RPTRA revitalization variable and street vendor arrangement on the happiness level of the city residents, F-count> F-table (246,889> 3,029)